Primary Peritonitis due to Group A Streptococcus in a Previously Healthy Pediatric Patient - R Holden; A Wilmer; T Kollman (Canadian Journal of Infectious Diseases and Medical Microbiology)
Primary peritonitis remains a rare disease in otherwise healthy children, with group A Streptococcus (GAS) being a particularly unusual cause. A case involving a 14-year-old girl, who presented with an ‘acute abdomen’ and was taken to the operating room for urgent laparoscopy, is reported. Abdominal and pelvic structures were only minimally inflamed, as was the appendix. Peritoneal fluid and blood cultures both grew pure cultures of GAS. The patient’s course was complicated by streptococcal toxic shock syndrome. She fortunately made a full recovery. The present report highlights the diagnostic and treatment dilemmas associated with GAS primary peritonitis.